A generalization of the Atkinson-Stiglitz (1976) Theorem on the undesirability of nonuniform excise taxation - Martin Hellwig (Max Planck Institute for Research on Collective Goods, 2008)
The Atkinson-Stiglitz (1976) theorem on the undesirability of nonuniform excise taxation when all agents have homogeneous, separable preferences is extended to allow for nonseparability with respect to endogenous variables that will be subject to distortions. The result is useful for analysing models with production and education. For such models, the conclusion of Bovenberg and Jacobs (2005), that it is desirable to distort production rather than education choices, is shown to be reversed if the hidden characteristic aþects the cost of education rather than productivity.
Keywords: H21; 330; Optimal Taxation; Atkinson-Stiglitz Theorem; Verbrauchsteuer; Optimale Besteuerung; Theorie